Exploring the Viability of Augmented Reality-based Cognitive Therapy of Poor Working Memory in Lifelong English for Medical Purposes (EMP) Comprehension: A Complementarity Study - Saeed Khazaie; Reza Torabi; Abbas Saghaei (Vesnu Publications, 2020)
Introduction: The aim of this study is to determine the effectiveness of cognitive therapy of poor working memory (WM) in students through self-generated augmented-reality (AR) based flipped English for Medical Purposes (EMP) reading classes on quality of students' academic and professional lives. Materials and Methods: This complementarity study was conducted using the semi-experimental method with a cross-contextual (continuous and real-workplace) assessment design along with soliciting attitudes and debriefing perception in the very initial and final phases, respectively. In the academic year 2018, after determining the WM capacities of 210 students of medicine from Medical University of Isfahan, Isfahan, Iran, they were randomly divided into seven heterogeneous groups with high visual and/or high verbal WM heads to practice EMP reading comprehension in 18 self-generated AR-based sessions; in each session, they were simultaneously assessed in both instructional-learning context and field. Results: Student active engagement in self-generating AR-based sessions spread the intrinsic cognitive load of EMP reading materials for students with low WM capacity, suggesting that students are inclined to active-participation courses. Conclusion: Student active participation in self-generating AR-based activities played a crucial role in cognitive therapy of students' psychological reading process and promoting EMP reading comprehension. However, the results should be viewed as suggestive.